New energy battery antimony-based negative electrode material and preparation method thereof
The antimony-based anode material prepared by the microemulsion method uses surfactant to achieve controllable flower-like structure. Combined with SbVO4 and carbon quantum dots, the energy loss and poor charging and discharge performance of the negative electrode materials of existing lithium-ion batteries are solved, and higher electrochemical performance and structural stability are achieved.
Patent Information
- Application Number
- CN202510223247.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-27
AI Technical Summary
The existing lithium-ion battery negative electrode materials such as carbon materials have problems such as energy loss, poor charging and discharging performance, and easy formation of passivation films, and it is easy to precipitate metal lithium during overcharging, causing short circuits.
The antimony-based negative electrode material was prepared by microemulsion method, and the controllable flower-like structure was achieved through the charge balance, template guidance, and dispersion stability mechanisms of cocamidopropyl betaine and sulfamic acid amphoteric surfactant, and a controllable composition combining SbVO4 and carbon quantum dots.
The good conductivity and special flower-like structure of the antimony-based negative electrode material are achieved, providing a large specific surface area to support electron transport, and alleviating the volume changes of the electrode material during circulation, improving structural stability.
Smart Images

Figure CN119725503A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of negative electrode materials, and in particular to an antimony-based negative electrode material for a new energy battery and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high voltage, good safety, long cycle life, no memory effect, and no pollution. They are one of the most widely studied new energy batteries. Their negative electrode materials are mostly graphite and various carbon materials, but studies have shown that carbon materials have disadvantages such as large energy loss and poor high-rate charge and discharge performance. In addition, carbon negative electrodes are prone to form passivation films in organic electrolytes, causing irreversible loss of initial capacity. The electrode potential of carbon materials is similar to that of metallic lithium. When the battery is overcharged, metallic lithium is easily precipitated on the surface of the carbon electrode, forming dendrites and causing short circuits. Therefore, finding better and more reliable new negative electrode materials for new energy batteries has become a research direction.
[0003] Research in recent years has shown that metallic antimony has an extremely high first theoretical lithium insertion capacity, and its lithium insertion potential is around 0.8V, which can effectively avoid the appearance of lithium dendrites and improve the safety performance of lithium-ion batteries. In addition, the lithium absorption and release process of antimony has a flat electrochemical reaction platform, which can provide a very stable operating voltage. Therefore, antimony-based negative electrode materials have aroused great interest among researchers. Chinese patent CN109473666A discloses a graphene-supported SbVO4 nanoparticle composite material and a preparation method thereof. The composite material has excellent electrochemical properties and exhibits high capacity and high rate performance when applied to lithium-ion batteries and sodium-ion batteries. The preparation method is simple and easy to mass produce. However, how to further improve the structure of antimony-based negative electrode materials, improve their electrochemical properties, and broaden their application scenarios has become a research hotspot for scientific researchers. Summary of the invention
[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes an antimony-based negative electrode material for new energy batteries and a preparation method thereof.
[0005] The technical solutions adopted are as follows: A method for preparing an antimony-based negative electrode material for a new energy battery is as follows: The carbon quantum dots, surfactant, n-butanol and cyclohexane are mixed to obtain an organic phase, and the organic phase is divided into two parts, which are recorded as organic phase A and organic phase B. Antimony trichloride aqueous solution and ammonium metavanadate aqueous solution are added to organic phase A and organic phase B respectively to obtain microemulsion A and microemulsion B. Microemulsion A and microemulsion B are mixed, stirred at room temperature for 1-5 hours, and then transferred to a hydrothermal reactor, sealed and heated to 140-160°C for 5-10 hours, and the reaction liquid is filtered after returning to room temperature, and the obtained product is washed with anhydrous ethanol and deionized water and then dried; The surfactant is composed of cocamidopropyl betaine and aminosulfonic acid type amphoteric surfactant; The mass ratio of the cocamidopropyl betaine to the aminosulfonic acid type amphoteric surfactant is 1-5:1-5; The structural formula of the aminosulfonic acid type amphoteric surfactant is as follows: ; Wherein, R1 and R2 are the same or different, and are each independently an alkyl group having ≥4 carbon atoms.
[0006] Furthermore, the antimony trichloride aqueous solution contains a hydrolysis inhibitor.
[0007] Furthermore, the hydrolysis inhibitor is hydrochloric acid.
[0008] Furthermore, R1 and R2 are the same, and are any one of n-butyl, n-pentyl, and n-butyl.
[0009] Furthermore, the preparation method of the aminosulfonic acid type amphoteric surfactant is as follows: ; S1: glycerol triglycidyl ether and 4-(dialkylamino)benzyl alcohol undergo a ring-opening reaction to obtain an intermediate; ; S2: The intermediate is subjected to a sulfonation reaction with 1,3-propane sultone to obtain the aminosulfonic acid type amphoteric surfactant.
[0010] Furthermore, the temperature of the sulfonation reaction in S2 is 40-60° C., and the time of the sulfonation reaction is 12-48 hours.
[0011] The present invention also provides an antimony-based negative electrode material for a new energy battery prepared by the above method, wherein the antimony-based negative electrode material is a composition of SbVO4 and carbon quantum dots, and the antimony-based negative electrode material has a flower-like structure.
[0012] Beneficial effects of the present invention: The present invention provides an antimony-based negative electrode material for a new energy battery, which is composed of SbVO4 and carbon quantum dots. The antimony-based negative electrode material has good conductivity and a special flower-like structure. The large specific surface area provides a continuous channel for electron transmission. At the same time, the volume change of the electrode material during the cycle can be alleviated, and the structural stability is improved. The negative electrode material is a new energy battery with great potential. When preparing antimony-based negative electrode materials through the microemulsion method, cocamidopropyl betaine and aminosulfonic acid-type amphoteric surfactants achieve the controllable preparation of flower-like structures through the three-in-one action mechanism of charge balance, template guidance, and dispersion stability. This can reduce side reactions and maintain the stability of the microemulsion during the high-temperature reaction process, ensuring the controllable synthesis of the negative electrode material morphology. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 This is the SEM image of the antimony-based negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0014] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.
[0015] Embodiment 1: An antimony-based negative electrode material for a new energy battery is a composition of SbVO4 and carbon quantum dots and has a flower-like structure.
[0016] The preparation method of the above-mentioned antimony-based negative electrode material for new energy batteries is as follows: 1g of sucrose was dissolved in 50ml of deionized water, stirred at room temperature for 30min, and then placed in a polytetrafluoroethylene autoclave for a sealed hydrothermal reaction at 180°C for 5h. After the hydrothermal reaction was completed, the temperature naturally dropped to room temperature. The solution was poured from the autoclave into a centrifuge tube and centrifuged at 12000r / min for 10min to precipitate large particles. The supernatant was poured out, and the solution was separated with a dialysis bag (500Da). Finally, the solution was freeze-dried for 48h to obtain carbon quantum dots. 0.01g carbon quantum dots, 2.5g cocamidopropyl betaine, 2.5g aminosulfonic acid type amphoteric surfactant, 10ml n-butanol, and 100ml cyclohexane were mixed to obtain an organic phase, and the organic phase was evenly divided into two parts, recorded as organic phase A and organic phase B. 5ml 0.1mol / L antimony trichloride aqueous solution and 5ml 0.1mol / L ammonium metavanadate aqueous solution were added to organic phase A and organic phase B respectively to obtain microemulsion A and microemulsion B, wherein the antimony trichloride aqueous solution was pre-adjusted to pH 2 with 0.1mol / L hydrochloric acid. Microemulsion A and microemulsion B were mixed, stirred at room temperature for 2h, and then transferred to a hydrothermal reactor, sealed and heated to 140°C for 10h, and the reaction solution was filtered after returning to room temperature. The obtained product was repeatedly washed with anhydrous ethanol and deionized water and then vacuum dried at 50°C for 24h. In order to study the morphology and microstructure of the antimony-based negative electrode material prepared for new energy batteries, it was observed by scanning electron microscopy. For details, see Figure 1; Among them, the structural formula of aminosulfonic acid type amphoteric surfactant is as follows: ; The specific preparation method is as follows: ; S1: Heat a mixed system of 0.1 mol of potassium metal and 0.9 mol of 4-(dibutylamino)benzyl alcohol to 70°C for reaction for 30 minutes, then slowly add 0.3 mol of propylene glycol triglycidyl ether, heat to 85°C after the addition is complete, and continue to react for 12 hours. After the reaction is completed, the system is cooled to room temperature, and the reaction solution is neutralized with 100 ml of 15% hydrochloric acid solution by mass, and then 1000 ml of dichloromethane and 1000 ml of water are added. After rapid stirring for 30 minutes, the organic layer is separated and dried with anhydrous magnesium sulfate, and small molecules are removed by vacuum distillation to obtain an intermediate; ; S2: Under nitrogen protection, add 0.01 mol of the intermediate and 0.04 mol of sodium hydride to 100 ml of dry tetrahydrofuran, stir and dissolve evenly, heat the water bath to 40°C, slowly drop 0.04 mol of 1,3-propane sultone, stir and react for 24 hours, remove the water bath, add 50 ml of methanol to remove the unreacted sodium hydride, concentrate under reduced pressure to remove small molecules, add 250 ml of deionized water, extract 3 times with 150 ml of n-butanol, combine the organic phases and concentrate under reduced pressure to obtain the aminosulfonic acid type amphoteric surfactant.
[0017] Embodiment 2: An antimony-based negative electrode material for a new energy battery is a composition of SbVO4 and carbon quantum dots and has a flower-like structure.
[0018] The preparation method of the above-mentioned antimony-based negative electrode material for new energy batteries is as follows: 1g of sucrose was dissolved in 50ml of deionized water, stirred at room temperature for 30min, and then placed in a polytetrafluoroethylene autoclave for a sealed hydrothermal reaction at 180°C for 5h. After the hydrothermal reaction was completed, the temperature naturally dropped to room temperature. The solution was poured from the autoclave into a centrifuge tube and centrifuged at 12000r / min for 10min to precipitate large particles. The supernatant was poured out, and the solution was separated with a dialysis bag (500Da). Finally, the solution was freeze-dried for 48h to obtain carbon quantum dots. 0.01g carbon quantum dots, 2.5g cocamidopropyl betaine, 2.5g aminosulfonic acid type amphoteric surfactant, 10ml n-butanol, and 100ml cyclohexane were mixed to obtain an organic phase, and the organic phase was evenly divided into two parts, recorded as organic phase A and organic phase B, and 5ml 0.1mol / L antimony trichloride aqueous solution and 5ml 0.1mol / L ammonium metavanadate aqueous solution were added to organic phase A and organic phase B respectively to obtain microemulsion A and microemulsion B, wherein the antimony trichloride aqueous solution was pre-adjusted to pH 2 with 0.1mol / L hydrochloric acid, microemulsion A and microemulsion B were mixed, stirred at room temperature for 2h, and then transferred to a hydrothermal reactor, sealed and heated to 150°C for 10h, and the reaction solution was filtered after returning to room temperature, and the obtained product was repeatedly washed with anhydrous ethanol and deionized water and then vacuum dried at 50°C for 24h; The structural formula and preparation method of the aminosulfonic acid type amphoteric surfactant are the same as those in Example 1.
[0019] Embodiment 3: An antimony-based negative electrode material for a new energy battery is a composition of SbVO4 and carbon quantum dots and has a flower-like structure.
[0020] The preparation method of the above-mentioned antimony-based negative electrode material for new energy batteries is as follows: 1g of sucrose was dissolved in 50ml of deionized water, stirred at room temperature for 30min, and then placed in a polytetrafluoroethylene autoclave for a sealed hydrothermal reaction at 180°C for 5h. After the hydrothermal reaction was completed, the temperature naturally dropped to room temperature. The solution was poured from the autoclave into a centrifuge tube and centrifuged at 12000r / min for 10min to precipitate large particles. The supernatant was poured out, and the solution was separated with a dialysis bag (500Da). Finally, the solution was freeze-dried for 48h to obtain carbon quantum dots. 0.01g carbon quantum dots, 2.5g cocamidopropyl betaine, 2.5g aminosulfonic acid type amphoteric surfactant, 10ml n-butanol, and 100ml cyclohexane were mixed to obtain an organic phase, and the organic phase was evenly divided into two parts, recorded as organic phase A and organic phase B, and 5ml 0.1mol / L antimony trichloride aqueous solution and 5ml 0.1mol / L ammonium metavanadate aqueous solution were added to organic phase A and organic phase B respectively to obtain microemulsion A and microemulsion B, wherein the antimony trichloride aqueous solution was pre-adjusted to pH 2 with 0.1mol / L hydrochloric acid, microemulsion A and microemulsion B were mixed, stirred at room temperature for 2h, and then transferred to a hydrothermal reactor, sealed and heated to 160°C for 10h, and the reaction solution was filtered after returning to room temperature, and the obtained product was repeatedly washed with anhydrous ethanol and deionized water and then vacuum dried at 50°C for 24h; The structural formula and preparation method of the aminosulfonic acid type amphoteric surfactant are the same as those in Example 1.
[0021] Comparative Example 1: It is basically the same as Example 1, except that no carbon quantum dots are added.
[0022] Comparative Example 2: The method is basically the same as Example 1, except that the preparation method of the antimony-based negative electrode material for new energy batteries is as follows: 1g of sucrose was dissolved in 50ml of deionized water, stirred at room temperature for 30min, and then placed in a polytetrafluoroethylene autoclave for a sealed hydrothermal reaction at 180°C for 5h. After the hydrothermal reaction was completed, the temperature naturally dropped to room temperature. The solution was poured from the autoclave into a centrifuge tube and centrifuged at 12000r / min for 10min to precipitate large particles. The supernatant was poured out, and the solution was separated with a dialysis bag (500Da). Finally, the solution was freeze-dried for 48h to obtain carbon quantum dots. 0.01g of carbon quantum dots, 5ml of 0.1mol / L antimony trichloride aqueous solution and 5ml of 0.1mol / L ammonium metavanadate aqueous solution were mixed, wherein the antimony trichloride aqueous solution was adjusted to pH 2 with 0.1mol / L hydrochloric acid, stirred for reaction at room temperature for 2h, then transferred to a hydrothermal reactor, sealed and heated to 140°C for reaction for 10h, and the reaction liquid was filtered after returning to room temperature. The product was repeatedly washed with anhydrous ethanol and deionized water and then vacuum dried at 50°C for 24h. In order to study the morphology and microstructure of the prepared antimony-based negative electrode material, it was observed by scanning electron microscopy, which showed that it was a nano-granular structure.
[0023] Performance Test: CR2025 button cells were prepared in a glove box filled with argon. The antimony-based negative electrode materials of new energy batteries prepared in Examples 1-3 of the present invention and Comparative Examples 1-2 were mixed with sodium alginate and acetylene black carbon powder in a mass ratio of 7:2:1 in an appropriate amount of water to produce electrode materials. The synthesized slurry was applied on a copper foil with a thickness of 150 μm, placed in a vacuum oven, and dried at 110° C. for 12 h. The electrodes were then punched into circular sheets with a diameter of 12 mm and pressed with a small tablet press at a pressure of 10 MPa to enhance the contact between the material and the copper foil. The diaphragm was made of Celgard 2300 membrane, pure lithium was used as the counter electrode, 1 mol lithium hexafluorophosphate was dissolved in 1L diethyl carbonate (DEC) / ethylene carbonate (EC) / dimethyl carbonate (DMC) mixed organic solvent (V(DEC): V(EC): V(DMC) = 1:1:1) as the electrolyte, the electrochemical performance was tested on the Blue Battery Test System, and the cyclic voltammetry (CV) test was performed on the CH1600E electrochemical workstation, the voltage was 0.05-3.00 V, the current density was 1A / g, and the test results are shown in Table 1 below:
[0024] It can be seen from Table 1 above that the antimony-based negative electrode material prepared by the present invention has relatively excellent electrochemical performance; By comparing Examples 1-3, it can be seen that the electrochemical properties of the antimony-based negative electrode materials prepared at different temperatures are slightly different. When the hydrothermal reaction temperature is 150°C, the antimony-based negative electrode material has the best electrochemical performance. By comparing Example 1 with Comparative Examples 1-2, it can be seen that the carbon quantum dots and the preparation method adopted by the present invention both play a positive role in improving the electrochemical performance of antimony-based negative electrode materials.
[0025] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an antimony-based negative electrode material for a new energy battery, characterized in that: The details are as follows: The carbon quantum dots, surfactant, n-butanol and cyclohexane are mixed to obtain an organic phase, and the organic phase is divided into two parts, which are recorded as organic phase A and organic phase B. Antimony trichloride aqueous solution and ammonium metavanadate aqueous solution are added to organic phase A and organic phase B respectively to obtain microemulsion A and microemulsion B. Microemulsion A and microemulsion B are mixed, stirred at room temperature for 1-5 hours, and then transferred to a hydrothermal reactor, sealed and heated to 140-160°C for 5-10 hours, and the reaction liquid is filtered after returning to room temperature, and the obtained product is washed with anhydrous ethanol and deionized water and then dried; The surfactant is composed of cocamidopropyl betaine and aminosulfonic acid type amphoteric surfactant; The mass ratio of the cocamidopropyl betaine to the aminosulfonic acid type amphoteric surfactant is 1-5:1-5; The structural formula of the aminosulfonic acid type amphoteric surfactant is as follows: ; Wherein, R1 and R2 are the same or different, and are each independently an alkyl group having ≥4 carbon atoms.
2. The method for preparing the antimony-based negative electrode material for new energy batteries according to claim 1, characterized in that: The antimony trichloride aqueous solution contains a hydrolysis inhibitor.
3. The method for preparing the antimony-based negative electrode material for new energy batteries according to claim 2, characterized in that: The hydrolysis inhibitor is hydrochloric acid.
4. The method for preparing the antimony-based negative electrode material for new energy batteries according to claim 1, characterized in that: R1 and R2 are the same and are any one of n-butyl, n-pentyl and n-butyl.
5. The method for preparing the antimony-based negative electrode material for new energy batteries according to claim 4, characterized in that: The preparation method of the aminosulfonic acid type amphoteric surfactant is as follows: ; S1: glycerol triglycidyl ether and 4-(dialkylamino)benzyl alcohol undergo a ring-opening reaction to obtain an intermediate; ; S2: The intermediate is subjected to a sulfonation reaction with 1,3-propane sultone to obtain the aminosulfonic acid type amphoteric surfactant.
6. The method for preparing the antimony-based negative electrode material for new energy batteries according to claim 5, characterized in that: The temperature of the sulfonation reaction in S2 is 40-60°C, and the time of the sulfonation reaction is 12-48h.
7. An antimony-based negative electrode material for a new energy battery prepared by the method for preparing an antimony-based negative electrode material for a new energy battery as claimed in any one of claims 1 to 6, characterized in that: The antimony-based negative electrode material is a composition of SbVO4 and carbon quantum dots, and the antimony-based negative electrode material has a flower-like structure.
Citation Information
Patent Citations
Preparation method of nano rare earth oxide powder
CN108083316A
Graphene supported SbVO4 nanoparticle composite material and preparation method thereof
CN109473666A
Preparation method of flower-like nickel protoxide, method for preparing anode lithium supplement agent Li2NiO2 by adopting flower-like nickel protoxide and application of anode lithium supplement agent Li2NiO2
CN118724088A
Antimony-based composite material and preparation method and application thereof
CN119390060A
Paste composition, heating element, heating apparatus, and method of manufacturing the paste composition
US20170158935A1